2020
DOI: 10.1007/s11684-020-0754-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq data analysis on the receptor ACE2 expression reveals the potential risk of different human organs vulnerable to 2019-nCoV infection

Abstract: It has been known that, the novel coronavirus, 2019-nCoV, which is considered similar to SARS-CoV and originated from Wuhan (China), invades human cells via the receptor angiotensin converting enzyme II (ACE2). Moreover, lung cells that have ACE2 expression may be the main target cells during 2019-nCoV infection. However, some patients also exhibit non-respiratory symptoms, such as kidney failure, implying that 2019-nCoV could also invade other organs. To construct a risk map of different human organs, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

68
1,940
3
90

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,095 publications
(2,197 citation statements)
references
References 18 publications
68
1,940
3
90
Order By: Relevance
“…1). Our results reveal that ACE2 expresses in lung AT2, liver cholangiocyte, colon colonocytes, esophagus keratinocytes, ileum ECs, rectum ECs, stomach epithelial cells, and kidney proximal tubules, consistent with the recent reports [6]. However, ACE2 expression levels are rather low in lung AT2 (4.7-fold lower than the average expression level of all ACE2 expressing cell types).…”
Section: Expression Atlas Of Ace2 Ssrna Viral Receptors and Other Mesupporting
confidence: 92%
See 2 more Smart Citations
“…1). Our results reveal that ACE2 expresses in lung AT2, liver cholangiocyte, colon colonocytes, esophagus keratinocytes, ileum ECs, rectum ECs, stomach epithelial cells, and kidney proximal tubules, consistent with the recent reports [6]. However, ACE2 expression levels are rather low in lung AT2 (4.7-fold lower than the average expression level of all ACE2 expressing cell types).…”
Section: Expression Atlas Of Ace2 Ssrna Viral Receptors and Other Mesupporting
confidence: 92%
“…As recently reported, both SARS-CoV-2 and SARS-CoV could use ACE2 protein to gain entry into the cells [4,5]. Since the outbreak, many data analysis have showed a wide distribution of ACE2 across human tissues, including lung, liver, stomach, ileum, colon and kidney [6], indicating that SARS-CoV-2 may infect multiple organs. However, these data showed that AT2 cell (the main target cell of SARS-CoV-2) in the lung actually expressed rather low levels of ACE2 [6].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The study of Xu et al 9 found that the RBD domain of the 2019-nCoV S-protein supports strong interaction with human ACE2 molecules. These findings suggest that the ACE2 plays an important role in cellular entry, thus ACE2-expressing cells may act as target cells and are susceptible to 2019-nCoV infection 10 .…”
Section: Introductionmentioning
confidence: 83%
“…Through the developed single-cell RNA sequencing (scRNA-Seq) technique and single-cell transcriptomes based on the public database, researchers analyzed the ACE2 RNA expression profile at single-cell resolution. High ACE2 expression was identified in type II alveolar cells (AT2) of lung [10][11][12] , esophagus upper and stratified epithelial cells, absorptive enterocytes from ileum and colon 12 , cholangiocytes 13 , myocardial cells, kidney proximal tubule cells, and bladder urothelial cells 10 . These findings indicated that those organs with high ACE2-expressing cells should be considered as potential high risk for 2019-nCoV infection 10 .…”
Section: Introductionmentioning
confidence: 99%